Exploring the orientation towards metaverse gaming: Contingent effects of VR tools usability, perceived behavioural control, subjective norms and age - Santanu Mandal; Ritesh Kumar Dubey; Bhaskar Basu; Anubhav Tiwari (Journal of Innovation & Knowledge (JIK), 2025)
The Gen-Z, who are deemed digital natives, have shown interest in the metaverse. The emergence of augmented reality (AR), virtual reality (VR), and mixed reality (XR) technologies in recent years has fuelled the increased interest in metaverse gaming. However, extant literature is yet to understand the individual orientations of these digital natives towards prime aspects of metaverse gaming and how it shapes one's attitude and, eventually, behavioural intentions for metaverse gaming. This study investigates the individual orientation towards social gaming, play for earn, flexibility gaming, and mixed reality as potential enablers for individuals' attitudes towards metaverse gaming. Using the well-established theory of planned behaviour (TPB), coupled with an extensive literature review, we explore the influence of attitude on behavioural intentions for metaverse gaming. The study also explores the contingent effects of VR tools' usability, subjective norms, perceived behavioural control, and age. We develop the measures for the used constructs through a literature review and pre-test before final data collection. Using an online questionnaire and purposive sampling, the study collected 308 and 256 complete responses from online gamers residing in South and East India, respectively, after fulfilling specific pre-decided filtering criteria. The findings of the study underscore the significant moderating effects of VR tools, subjective norms, perceived behavioural control, and age towards metaverse gaming. The findings highlight the far-reaching implications for policymakers and practitioners. Companies can leverage this mix of demography and technology for immersive experiences for new marketing, branding, and loyalty programs. Policymakers may underscore the cyber threats and prepare for regulatory and legal challenges.
Keywords: M15; M31; 650; Metaverse; Virtual gaming; Play to earn; Mixed reality; Perceived behavioural control; Digital native